2019
DOI: 10.5194/amt-12-3673-2019
|View full text |Cite
|
Sign up to set email alerts
|

The Mineral Aerosol Profiling from Infrared Radiances (MAPIR) algorithm: version 4.1 description and evaluation

Abstract: The Mineral Aerosol Profiling from Infrared Radiances (MAPIR) algorithm retrieves vertical dust concentration profiles from cloud-free Infrared Atmospheric Sounding Interferometer (IASI) thermal infrared (TIR) radiances using Rodgers' optimal estimation method (OEM). We describe the new version 4.1 and evaluation results. Main differences with respect to previous versions are the Levenberg-Marquardt modification of the OEM, the use of the logarithm of the concentration in the retrieval and the use of Radiative… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…The most obvious one is the CALIPSO dataset, which has been observing the global aerosol distribution since 2006 (Winker et al, 2010;Tsamalis et al, 2013), and in the future Earth-CARE is expected to be another very good candidate (Illingworth et al, 2015). Note that this perspective is not limited to using active sensors, and studies exist on the observation of the vertically resolved distribution from passive hyperspectral instruments in the infrared (Callewaert et al, 2019). In the long term, providing observations not only of AOD, but also of the vertical distribution of aerosols, could become the driver for operational space missions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The most obvious one is the CALIPSO dataset, which has been observing the global aerosol distribution since 2006 (Winker et al, 2010;Tsamalis et al, 2013), and in the future Earth-CARE is expected to be another very good candidate (Illingworth et al, 2015). Note that this perspective is not limited to using active sensors, and studies exist on the observation of the vertically resolved distribution from passive hyperspectral instruments in the infrared (Callewaert et al, 2019). In the long term, providing observations not only of AOD, but also of the vertical distribution of aerosols, could become the driver for operational space missions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies which have looked at this issue more comprehensively do, however, suggest that there is an underprediction of wind fields in the models, which is also linked to coarse-resolution modelling (e.g. Chouza et al, 2016). Evan et al (2016) showed that desert dust emission is to first order a function of wind speed, and it is against this quantity that models parameterise the dust source.…”
Section: Effect Of Large-scale Wind and Boundary Layer Heightmentioning
confidence: 99%
See 2 more Smart Citations
“…Adapted from Cuesta et al (2009) [Colour figure can be viewed at wileyonlinelibrary.com] et al, 2010) and IASI (Infrared Atmospheric Sounding Interferometer; Kylling et al, 2018). Vertical profiles of dust load have been derived from IASI, initially over ocean with limited coverage over land (Vandenbussche et al, 2013) and more recently over both land and ocean (Cuesta et al, 2015;Callewaert et al, 2019). Moreover, IASI measurements have enabled the first 3D observations of both the vertical distribution and the horizontal structure of dust plumes with full coverage for cloud-free conditions, on a daily basis and over all surfaces (both land and ocean) using the so-called AEROIASI approach (Cuesta et al, 2015).…”
Section: Introductionmentioning
confidence: 99%